Langley method applied in study of aerosol optical depth in the Brazilian semiarid region using 500, 670 and 870 nm bands for sun photometer calibration - Cerqueira Júnior, J.G. (2020)
Due to the high costs of commercial monitoring instruments, a portable sun photometer was developed at INPE/CRN laboratories, operating in four bands, with two bands in the visible spectrum and two in near infrared. The instrument calibration process is performed by applying the classical Langley method. Application of the Langley’s methodology requires a site with high optical stability during the measurements, which is usually found in high altitudes. However, far from being an ideal site, Harrison et al. (1994) report success with applying the Langley method to some data for a site in Boulder, Colorado. Recently, Liu et al. (2011) show that low elevation sites, far away from urban and industrial centers can provide a stable optical depth, similar to high altitudes. In this study we investigated the feasibility of applying the methodology in the semiarid region of northeastern Brazil, far away from pollution areas with low altitudes, for sun photometer calibration. We investigated optical depth stability using two periods of measurements in the year during dry season in austral summer. The first one was in December when the native vegetation naturally dries, losing all its leaves and the second one was in September in the middle of the dry season when the vegetation is still with leaves. The data were distributed during four days in December 2012 and four days in September 2013 totaling eleven half days of collections between mornings and afternoons and by means of fitted line to the data V0 values were found. Despite the high correlation between the collected data and the fitted line, the study showed a variation between the values of V0 greater than allowed for sun photometer calibration. The lowest V0 variation reached in this experiment with values lower than 3% for the bands 500, 670 and 870 nm are displayed in tables. The results indicate that the site needs to be better characterized with studies in more favorable periods, soon after the rainy season